Adiponectin receptor 1-mediated stimulation of Cav3.2 channels in trigeminal ganglion neurons induces nociceptive behaviors in mice - Yuan Zhang; Yuan Wei; Tingting Zheng; Yu Tao; Yufang Sun; Dongsheng Jiang; Jin Tao (The Journal of Headache and Pain, 2023)
Abstract Background Adipokines, including adiponectin, are implicated in nociceptive pain; however, the underlying cellular and molecular mechanisms remain unknown. Methods Using electrophysiological recording, immunostaining, molecular biological approaches and animal behaviour tests, we elucidated a pivotal role of adiponectin in regulating membrane excitability and pain sensitivity by manipulating Cav3.2 channels in trigeminal ganglion (TG) neurons. Results Adiponectin enhanced T-type Ca2+ channel currents (I T) in TG neurons through the activation of adiponectin receptor 1 (adipoR1) but independently of heterotrimeric G protein-mediated signaling. Coimmunoprecipitation revealed a physical association between AdipoR1 and casein kinase II alpha-subunits (CK2α) in the TG, and inhibiting CK2 activity by chemical inhibitor or siRNA targeting CK2α prevented the adiponectin-induced I T response. Adiponectin significantly activated protein kinase C (PKC), and this effect was abrogated by CK2α knockdown. Adiponectin increased the membrane abundance of PKC beta1 (PKCβ1). Blocking PKCβ1 pharmacologically or genetically abrogated the adiponectin-induced I T increase. In heterologous expression systems, activation of adipoR1 induced a selective enhancement of Cav3.2 channel currents, dependent on PKCβ1 signaling. Functionally, adiponectin increased TG neuronal excitability and induced mechanical pain hypersensitivity, both attenuated by T-type channel blockade. In a trigeminal neuralgia model induced by chronic constriction injury of infraorbital nerve, blockade of adipoR1 signaling suppressed mechanical allodynia, which was prevented by silencing Cav3.2. Conclusion Our study elucidates a novel signaling cascade wherein adiponectin stimulates TG Cav3.2 channels via adipoR1 coupled to a novel CK2α-dependent PKCβ1. This process induces neuronal hyperexcitability and pain hypersensitivity. Insight into adipoR-Cav3.2 signaling in sensory neurons provides attractive targets for pain treatment.